CAROTENE YIELD IN SWEET POTATO AFTER POTASSIUM AND PHOSPHORUS FERTILISER APPLICATION - Cruz Nascimento, Sandra Maria (2019)
Sweet potato is one of the most important foods in the world. Among the different cultivated genotypes, it is worth highlighting those with orange pulp due to their ability to supply adequate amounts of provitamin A carotenoids to humans. This study evaluates the effect of potassium and phosphorus fertiliser application on carotenoid yield in sweet potatoes. Two experiments were carried out in Sao Luis City, Maranhao State, Brazil. The experimental design was a randomised block design, with six treatments for each of the studies (0, 30, 60, 90, 120 and 150 kg ha(-1) K2O and 0, 60, 120, 180, 240 and 300 kg ha(-1) P2O5), with four replicates. Cultivar 'Beauregard' was used, which has high levels of carotenoids. Roots were harvested at 123 days after planting for both experiments. The following variables were evaluated: root fresh and dry weight, dry weight content, in addition to the yield and contents of total carotenoids, alpha-carotene, beta-carotene, 13-cis beta-carotene and 9-cis beta-carotene. With the average data of the evaluated characteristics, we performed analysis of variance and polynomial regression analysis. Potassium rates influenced carotenoid yield in sweet potato roots, with the rates of 73 to 77 kg ha(-1) K2O being recommended to maximise the production of total carotenoids, 0carotene, and a-carotene. Phosphorus, in turn, influenced only total carotenoids, and is recommended at the rate of 174.09 kg ha(-1) P2O5 to maximise the production of these nutrients.